MULTI-SENSOR FUSION TECHNOLOGY FOR CREATING IMMERSIVE OUTDOOR VISUAL ART EXPERIENCES - Prajapati, Arpita A.; Panneerselvam, Ponmurugan; Sule, Bipin; Nisha A, Sahaya Anselin; Ghosh, Debanjan; Gupta, Mridula; Rani G, Asha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Multi-sensor fusion technology has become a groundbreaking methodology of developing immersive outdoor visual art experiences through the process of combining heterogeneous data into adaptive systems of art. This paper introduces a general concept of a multi-sensor fusion-based art system, which uses visual (RGB-D cameras), motion (IMU), spatial (LiDAR), environmental (temperature, humidity, light), and biometric sensors to support dynamic, context-responsive art-related interactions in the outdoor setting. The suggested methodology makes use of multi-modal feature extraction as a way of visual patterns, motion dynamics, and environmental changes and then applies a hybrid fusion algorithm combining deep learning architectures and statistical models to provide a superior data synthesis and responsiveness to real-time requirements. A time-dependent collection unit assures time synchronization of sensor streams, improving the reliability of the system in different application tasks in the outdoor environment. The results of the experimental assessment show that these systems are much more accurate, responsive and user-engaging in comparison to single sensor and baseline systems. The findings point to improved spatial awareness and adaptive content creation, as well as fidelity of interaction, as a part of an increasingly immersive and individually-centered artistic experience.